Vaccinia virus intracellular mature virions contain only one lipid membrane. - Hollinshead, M; Vanderplasschen, A; Smith, G; Vaux, D (1999)
Vaccinia virus (VV) morphogenesis commences with the formation of lipid crescents that grow into spherical immature virus (IV) and then infectious intracellular mature virus (IMV) particles. Early studies proposed that the lipid crescents were synthesized de novo and matured into IMV particles that contained a single lipid bilayer (S. Dales and E. H. Mosbach, Virology 35:564-583, 1968), but a more recent study reported that the lipid crescent was derived from membranes of the intermediate compartment (IC) and contained a double lipid bilayer (B. Sodiek et al., J. Cell Biol. 121:521-541, 1993). In the present study, we used high-resolution electron microscopy to reinvestigate the structures of the lipid crescents, IV, and IMV particles in order to determine if they contain one or two membranes. Examination of thin sections of Epon-embedded, VV-infected cells by use of a high-angular-tilt series of single sections, serial-section analysis, and high-resolution digital-image analysis detected only a single, 5-nm-thick lipid bilayer in virus crescents, IV, and IMV particles that is covered by a 8-nm-thick protein coat. In contrast, it was possible to discern tightly apposed cellular membranes, each 5 nm thick, in junctions between cells and in the myelin sheath of Schwann cells around neurons. Serial-section analysis and angular tilt analysis of sections detected no continuity between virus lipid crescents or IV particles and cellular membrane cisternae. Moreover, crescents were found to form at sites remote from IC membranes-namely, within the center of virus factories and within the nucleus-demonstrating that crescent formation can occur independently of IC membranes. These data leave unexplained the mechanism of single-membrane formation, but they have important implications with regard to the mechanism of entry of IMV and extracellular enveloped virus into cells; topologically, a one-to-one membrane fusion suffices for delivery of the IMV core into the cytoplasm. Consistent with this, we have demonstrated previously by confocal microscopy that uncoated virus cores within the cytoplasm lack the IMV surface protein D8L, and we show here that intracellular cores lack the surface protein coat and lipid membrane.